Adherence to Antiretroviral Theraphy and Associated Factors Among People Living with HIV in Surakarta - Evi Nurhayatun; Mila Ulfia; Tirsa Angelina (JURNAL INFO KESEHATAN, 2025)
The Human Immunodeficiency virus (HIV) presents a major public health challenge due to its association with high mortality and morbidity rates. Infection HIV occurs when the virus attacks the body’s immune system at a cellular level. Without treatment, this can progress to the most advanced stage, Acquired Immune Deficiency Syndrome (AIDS). For people living with HIV (PLWHIV), lifelong treatment with antiretroviral (ARV) medication is necessary. This continuing therapy works to reduce the amount of virus in the blood, lowering the risk of transmission, preventing secondary infections, and improving the patient's general life quality. The success and effectiveness of ARV therapy depends on PLWHIV adherence. Poor adherence to antiretroviral therapy decreases its effectiveness and increases viral replication. Therapy adherence indicates that the patient understands the value of receiving therapy and follows the instructions. Knowledge is an important role in therapy compliance. This cross-sectional study was conducted at the VCT Polyclinic of the Department of Internal Medicine, Dr. Moewardi General Hospital in Surakarta, between April and July 2024. The target population included all patients who received a positive HIV diagnosis. A total of 60 patients from this group were selected to participate using a purposive sampling strategy. Bivariate analysis was then used to investigate the relationship between variables, with the Spearmean Rank statistical test.  The study result showed that 21 patients with poor level of knowledge had low compliance (92.9%), followed by patients with intermediate level of knowledge with moderate compliance 10 (60.0%), and patients with high level of knowledge with high compliance 29 (69.4%). A statistically significant, moderately strong positive relationship (r=0.572, p < 0.001) was found between patient knowledge and adherence to ARV therapy at the VCT polyclinic of Dr. Moewardi Hospital, Surakarta. This suggests that PLWHIV who receive adequately informed patients are more likely to adhere to their treatment plans. Therefore, improving patient compliance requires implementing robust educational programs and conducting further research to uncover other influencing factors.